Oculocerebral hypopigmentation syndrome (Cross syndrome) - Özkan, Hasan; Ünsal, Erbil; Köse, Galip (The Turkish Journal of Pediatrics, 1991)
A typical case of Cross syndrome with hypopigmentation, mental and psychomotor retardation, spasticity, bilateral optic atrophy and dental defects in a three-year-old boy is presented. The clinical features of this rare syndrome are discussed.
Keywords: Cross syndrome; albinism